Bovine Trypanosomosis in three districts of East Gojjam Zone bordering the Blue Nile River in Ethiopia - Adane Mihret,1,2 Gezahagne Mamo,3 (The Journal of Infection in Developing Countries, 2007)
Background: Bovine trypanosomosis is a serious constraint to agricultural production in extensive areas of Ethiopia.Methodology: A cross-sectional study was conducted to determine the prevalence of bovine infection with trypanosomes and to identify the prevailed trypanosome species in three districts of the East Gojjam zone bordering the Blue Nile River from March 2005 to February 2006. Cattle from 9 different localities were checked using microscopical examination of wet blood smears, thin and stained bloodsmears, and by blood centrifugation followed by the examination of the resultant buffy coats.Result: Of the total 3,360 cattle investigated, 8.2% (3.5%, 11.6% and 9.4% from Dejen, Machakel and Baso-Liben districts respectively) were found to be infected with trypanosomes. Of the total 275 positive animals, 249 (90.5%) appeared to be infected with Trypanosoma vivax; 11 (4%) were infected with T. congolense; and 15 (5.5%) were infected with mixed infection of T. vivax and T. congolense. The prevalence of infection with T. vivax was significantly higher than that of T. congolense (P <0.001). Taking 24-46% as normal PCV value, the mean PCV for the trypanosome-infected cattle (22.09%) was lower than those for the trypanosome-negative animals (26.03).Conclusion: Trypanosomosis is a disease of considerable importance to the major economic districts bordering the Blue Nile River of the East Gojjam zone, Ethiopia, given the disease's potential to threaten the health and productivity of cattle in this region.